Living resistance : an Indigenous vision for seeking wholeness every day - Curtice, Kaitlin B. (Brazos Press, a division of Baker Publishing Group, 2023)
"Popular Indigenous author Kaitlin Curtice argues that resistance isn't just for professional activists but for every human who longs to see their neighbors' holistic flourishing."--